2022
DOI: 10.3389/feart.2021.829258
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Fracturing Characteristics of Double-Hole Blasting Under Static Stresses

Abstract: This study aims to investigate the fracturing characteristics of double-hole blasting under the action of coupled static stress and delayed time explosion. A total of thirteen explosive tests were carried out on rectangular concrete blocks with different constraints. The test blocks were wrapped in steel mesh in the test bed to prevent flying away of the cracked blocks after blasting. After blasting, the surface area of the crater was measured, and all pieces of the cracked blocks were collected, screened, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Jayasinghe et al 10 proposed a three-dimensional coupled smooth particle hydrodynamics and finite element methods to study the influence of discontinuous high in-situ stress on the evolution of rock multi-hole blasting damage. Chen et al 11 carried out fifteen multi-hole blasting tests on rectangular concrete blocks under different constraints by orthogonal test method, then explored the fracture characteristics of multi-hole blasting rock under the coupling action of static stress and delay time. Based on the engineering background of gas extraction in low permeability coal seam, Liu et al 12 developed single-hole, double-hole and pilot-hole blasting tests to discuss the influence of hole arrangement on static blasting.…”
Section: Introductionmentioning
confidence: 99%
“…Jayasinghe et al 10 proposed a three-dimensional coupled smooth particle hydrodynamics and finite element methods to study the influence of discontinuous high in-situ stress on the evolution of rock multi-hole blasting damage. Chen et al 11 carried out fifteen multi-hole blasting tests on rectangular concrete blocks under different constraints by orthogonal test method, then explored the fracture characteristics of multi-hole blasting rock under the coupling action of static stress and delay time. Based on the engineering background of gas extraction in low permeability coal seam, Liu et al 12 developed single-hole, double-hole and pilot-hole blasting tests to discuss the influence of hole arrangement on static blasting.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al 11 used LS-DYNA numerical simulation analysis to compare and study cracks propagation of double-hole detonation and penetration phenomenon of cracks in elliptical bipolar linear charging explosion and general explosion, which found that the former seriously influences directional crack’s formation. Chen et al 12 studied fracturing characteristics under coupling action of static pressure and delay blasting based on the concrete double-hole explosion test, and found that fragmentation degree after detonation is tightly associated with the two factors. Zhang et al 13 used the ANASYS/LS-DYNA coupling method to simulate the two hole blasting of slit charge under two-way equal pressure and two-way different pressure under high ground stress.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they are valuable for validating various numerical simulation codes, making them commonly employed for rock fragmentation and fracture testing [8,22,[27][28][29][30][31][32][33][34][35], as well as for dynamic impact studies of brittle materials such as rocks [36][37][38]. In the past, small-scale model tests focused primarily on studying rock fragmentation mechanisms, fragment size analysis, and blasting crater analysis [39][40][41][42][43][44]. There has been limited research on the influence of stemming length and material on the dynamic strain response of test block surfaces, and few studies have addressed the measurement of stemming material recoil and ejection extent.…”
Section: Introductionmentioning
confidence: 99%